System- and Data-Driven Methods and Algorithms - Benner, Peter; Grivet-Talocia, Stefano; Quarteroni, Alfio; Rozza, Gianluigi; Schilders, Wil; Silveira, Luís Miguel (Model Order Reduction, 2021)
An increasing complexity of models used to predict real-world systems leads to the need for algorithms to replace complex models with far simpler ones, while preserving the accuracy of the predictions. This two-volume handbook covers methods as well as applications. This first volume focuses on real-time control theory, data assimilation, real-time visualization, high-dimensional state spaces and interaction of different reduction techniques.